Solid Microcystic Adnexal Carcinoma on the Thigh: An Unusual Location. (February 2020) - Diago, Adrián; Requena, Luis; Traves, Víctor; Requena, Celia
Abstract : Abstract: Solid carcinoma, probably the solid variant of microcystic adnexal carcinoma, is an apocrine adnexal tumor first described in 1998. The authors report an additional new case of the tumor at an unusual localization. A 78-year-old man presented with an asymptomatic firm plaque on his right thigh that had been present for 15 years. A biopsy was taken, and then, the lesion was removed. A pathological study showed a huge number of islands made up of aggregations of neoplastic epithelial cells. The epithelial islands showed variable sizes and shapes at scanning magnification, arranged columns, cords, and strands at the basis of the tumor. The neoplastic cells were embedded within a fibrotic stroma. Ductal differentiation, cystic structures, and neurotropism were also observed. Immunohistochemically, the neoplastic cells expressed high–molecular-weight keratin (cytokeratin 5/6), broad-spectrum keratin (AE1/AE3), p40, and p63. No immunoreactivity was found for BerEP4, cytokeratin 7, cytokeratin 19, cytokeratin 20, chromogranin A, carcinoembryonic antigen, and S-100. The lesion was completely removed with slow-Mohs micrographic surgery. Two stages and previous debulking were necessary to obtain free margins. The second stage included the muscular fascia. The patient remains free of tumor after a year of follow-up. Solid microcystic adnexal carcinoma is a rare skin tumor that seems to occur more frequently in the scalp than in the face, but no area of the body can be excluded, as reported in our case. Differential diagnosis should include sclerosing and clear-cell basal cell carcinoma, clear-cell dermal duct tumor, or desmoplastic trichoepithelioma. Mohs micrographic surgery is the treatment of choice.